Individual wealth accumulation: Why does dining together as a family matter? - Swarn Chatterjee; Lance Palmer; Joseph Goetz (Applied Economics Research Bulletin, 2012)
This study uses data from the Panel Study of Income Dynamics to examine whether self-regulation, proxied by regularly dining together with family, is associated with better financial preparedness and greater wealth accumulation across time among households. Findings reveal that individuals who had sufficient self-regulation to regularly eat meals together with their family, increased wealth at a faster rate than others between 1994 and 2004. Moreover, those who exhibited self-regulation by frequently spending mealtime with their family showed greater preference for investment portfolio diversification. Consistent with other studies, results indicate that wealth accumulation increased with age, income, and educational attainment.
Keywords: D14; D31; D91; D03; 330; Individual wealth; Behavioral Economics; Portfolio Allocation; Self Regulation; Wealth; Behavioral economics; Portfolio selection; Self-Regulation